The Stop Tuberculosis Partnership - Independent Evaluation Group (Washington, DC: World Bank, 2017)
The stop Tuberculosis (TB) partnership is a network of international organizations, countries, governmental and nongovernmental organizations, public and private sector donors, and individuals dedicated to the elimination of tuberculosis as a public health problem. The partnership is a loose coalition of partners working to elevate action on tuberculosis, one of the leading causes of death from infectious disease, on the global agenda. The stop TB partnership was formally established in 2001, as it became clear to the international community that the initial targets set for TB control in 1991.The specific objectives for which the partnership has been accountable have evolved somewhat since 2001, and have recently been stated most clearly in the global plan to stop TB, 2006-2015. Since the present Global Program Review (GPR) covers the period from the initiation of the program to the present, it has reviewed the achievements of the stop TB partnership against four objectives which have been synthesized from core partnership documents going back to 2001, namely: 1) to expand the Directly Observed Treatment Short-Course (DOTS) strategy so that all people have access to effective diagnosis and treatment; 2) to develop and scale-up effective responses to the emerging challenges of drug resistance and HIV-related TB; 3) to improve and expand tools available for TB diagnosis, treatment and prevention; and 4) to strengthen the overall global partnership to stop TB so that proven TB-control strategies are effectively applied.